Dividend Trap: Impact of Yield, Volume, and Payout on Investments - Natalia, Karisma; Kohardinata, Cliff (Program Studi Akuntansi FPEB UPI, 2024)
This study aims to obtain empirical test results regarding the effect of dividend yield, stock volume, and dividend payout ratio on dividend trap. This study uses secondary data for 2022-2023 using a dividend distribution schedule in 2023. The sampling technique was purposive sampling and obtained 223 company stock observation data in various industrial sectors. The research method uses panel data regression using the Stata 13 program. The test results in this study indicate that there is a positive significant effect of dividend yield and stock volume on dividend trap, and a negative significant effect of dividend payout ratio on dividend trap. This research provides a new understanding of the risk of dividend trap for dividend-focused investors, highlighting the importance of choosing company stocks efficiently.